2017
DOI: 10.1103/physrevb.96.125423
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo approach to nonequilibrium bosonic systems

Abstract: We consider the use of a Kinetic Monte Carlo approach for the description of non-equilibrium bosonic systems, taking non-resonantly excited exciton-polariton condensates and bosonic cascade lasers as examples. In the former case, the considered approach allows the study of the cross-over between incoherent and coherent regimes, which represents the formation of a quasi-condensate that forms purely from the action of energy relaxation processes rather than interactions between the condensing particles themselve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…As our system essentially amounts to a gain medium, with population inversion, located in a cavity it could also be considered a THz laser. A coherent statistics would be expected of the emission [29], although we do not calculate it here, restricting ourselves to a semiclassical theory.…”
mentioning
confidence: 99%
“…As our system essentially amounts to a gain medium, with population inversion, located in a cavity it could also be considered a THz laser. A coherent statistics would be expected of the emission [29], although we do not calculate it here, restricting ourselves to a semiclassical theory.…”
mentioning
confidence: 99%
“…However, studies of exciton dynamics showed that the radiative cascade wasn't the dominant relaxation mechanism [71,84]. A recent theoretical study tried to explain this suppression of the radiative transitions and proposed a new alternative scheme based on double QW structures [84]. Nevertheless, we showed that excitons relax much faster in the parabolic potential compared to a structure with conventional rectangular QWs.…”
Section: Overview and Final Thoughtsmentioning
confidence: 80%
“…This part was based on the proposal of a BCL [51]. However, studies of exciton dynamics showed that the radiative cascade wasn't the dominant relaxation mechanism [71,84]. A recent theoretical study tried to explain this suppression of the radiative transitions and proposed a new alternative scheme based on double QW structures [84].…”
Section: Overview and Final Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower density of states and the consequently weaker energy relaxation processes needed higher quality factor microcavities to provide a longer lifetime to compensate and achieve polariton condensation [56]. Theoretical calculations show that in 1D, the inuence of polariton-phonon scattering is very small and that the condensation here is dominated by other factors such as polaritonexciton scattering [57].…”
Section: Dos Parabolic Linearmentioning
confidence: 99%